Subsistence strategies throughout the African Middle Pleistocene: Faunal evidence for behavioral change and continuity across the Earlier to Middle Stone Age transition. Issue 127 (February 2019) - Smith, Geoff M.; Ruebens, Karen; Gaudzinski-Windheuser, Sabine; Steele, Teresa E.
Abstract: The African Middle Pleistocene (781–126 ka) is a key period for human evolution, witnessing both the origin of the modern human lineage and the lithic turnover from Earlier Stone Age (ESA) Acheulean bifacial tools to Middle Stone Age (MSA) prepared core and point technologies. This ESA/MSA transition is interpreted as representing changing landscape use with greater foraging distances and more active hunting strategies. So far, these behavioral inferences are mainly based on the extensive stone tool record, with only a minor role for site-based and regional faunal studies. To provide additional insights into these behavioral changes, this paper details a pan-African metastudy of 63 Middle Pleistocene faunal assemblages from 40 sites. A hierarchical classification system identified 26 well-contextualized assemblages with quantitative paleontological and/or zooarcheological data available for detailed comparative analyses and generalized linear mixed modeling. Modeling of ungulate body size classes structured around three dimensions (context, antiquity and technology) illustrates no one-to-one correlation between changes in lithic technology (Acheulean vs. MSA) and changes in prey representation. All assessed faunal assemblages are dominated by medium-sized bovids, and variations between smaller and larger body size classes are linked to site context (cave vs. open-air), with an increase in cave sites during the Middle Pleistocene. Current data do not signal a broadening of the hominin dietary niche during the Middle Pleistocene; no meaningful variation was visible in the exploitation of smaller-sized bovids or dangerous game, with coastal resources exploited when available. Proportions of anthropogenic bone surface modifications, and hence carcass processing intensity, do increase over time although more zooarcheological data is crucial before making behavioral inferences. Overall, this paper illustrates the potential of broad scale comparative faunal analyses to provide additional insights into processes of human behavioral evolution and the mechanisms underlying patterns of technological, chronological and contextual change.